Keragaan Stek Pucuk Syzygium oleina terhadap Pemberian Zat Pengatur Tumbuh Rootone-F dan Komposisi Media Tanam - Deselina, Deselina; Hidayat, M. Fajrin; Wiratama, Ganesya (Akta Agrosia, 2015)
This study aims to determine the concentration of plant growth regulator combination Rootone F and a growing medium that provides the best growth of Pucuk Merah shoot cuttage. The research was conducted on the July to September 2013. The method used is Complete Random Design (RAL) factorial consisting of two factors. The first factor is the concentration of plant growth regulators Rootone-F (R), which consists of four levels: 0 ppm (control), 100 ppm (R1), 150 ppm (R2) and 200 ppm (R3). The second factor is the composition of the growing medium consists of: ground (M1), soil, sand (1: 1) (M2), soil: sand: compost (1: 1: 1) (M3). The variables measured were successful life cuttage, leaf number, root length, number of secondary roots and dry weight of cuttings and environmental factors (temperature and humidity). Results of analysis of variance showed that the concentration of plant growth regulators Rootone-F only real impact on the number of secondary roots while growing medium treatment showed no real effect on all observed variables. Combination treatment of concentration of growth regulators Rootone-F and planting media show no real effect on all observed variables. The ambient ttemperature during the study was C 27.85-30.47 and humidity 93.48-96.32%. Based on the results of analysis show that the combined treatment P2M2 gives the average percentage of success alive and rooted cuttings highest 73.3%, number of leaves 2 strands, 4.07 cm root length, 2 number of secondary roots and root dry weight 0.56 g.?